Kewenangan Pemerintah Kota Denpasar dalam Penerapan Jalur Khusus Sepeda - I Putu Aldi Wira Kusuma; I Nyoman Gede Sugiartha; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
Realizing an environmentally friendly city of Denpasar is one of the balancing concepts in the development of an environmentally friendly city. Changing the mode of transportation to environmentally friendly transportation, such as the use of bicycles, can prevent congestion. One of the government's real actions is the government's authority on bicycle lanes as a necessity for the community. The purposes of this study are to reveal the form of authority of the Denpasar City Government in Streamlining the Application of Bicycle Paths and forms of legal protection for bicycle lane users based on Law Number 22 Year 2009 in Denpasar City. The type of legal research used in this research is empirical legal research with a statutory approach. The data collection techniques were carried out by reading, recording, quoting, summarizing and analyzing the data and information obtained from the relevant agencies, namely the Denpasar City Transportation Service. After obtaining primary legal materials and secondary legal materials which are then processed and analyzed systematically, data is obtained that the authority of the Denpasar City government in making the use of bicycle lanes effective is to provide bicycle lane facilities at several points scattered in the Denpasar City area, such as on Jalan Sudirman , Jalan Letda Made Putra, Jalan Letda Tantular and at several other points. Meanwhile, legal protection for bicycle lane users contains the rights of bicycle lane users, such as the mandatory provision of bicycle lane facilities by the government to ensure the safety and comfort of cyclists, freedom from fear in traffic, and avoidance of traffic hazards.